Analysis of Factors Related to the Performance of Health Workers at the Royal Prima Medan General Hospital in 2022 - Dendy Teguh Kurniawan; Sri Lestari; Yolanda Eliza Putri Lubis (International Journal of Health and Pharmaceutical (IJHP), 2023)
The performance of health workers at RSU Royal Prima is experiencing a fluctuating trend so that it is still not optimal in providing services to patients and organizational responsibilities. Factors that are suspected to be related to the performance of health workers are individual, psychological, and organizational variables. This study aims to analyze the factors related to the performance of health workers. This type of research is quantitative analytic using a cross sectional design. The research was conducted at RSU Royal Prima Medan. The research population was 651 people, while the sample was 100 people. Sampling by means of simple random sampling. Data were analyzed using univariate, bivariate with chi-square test, and multivariate with multiple logistic regression at 95% confidence level (=0.05). The results showed that the factors related to the performance of health workers at RSU Royal Prima Medan were abilities and skills (p=0.015), motivation (p=0.033), leadership (p=0.024), and rewards (p=0.044). Factors that were not related were age (p=1.000), gender (p=1.000), perception (p=0.240), attitude (p=0.163), and job design (p=0.464). The most dominant variable relates to the performance of health workers, namely leadership. Health workers who stated good leadership had the opportunity to have good performance 8.2 times higher than health workers who stated poor leadership. It is recommended that the management of RSU Royal Prima Medan conduct continuous performance assessments of health workers.